Model of State Defense Strengthening Responding to the Impact of Eliminating the Presidential Threshold in Order to Realize Inclusive Democracy - Cecilia Cecilia; Faonaso Harefa (Green Publisher Indonesia, 2025)
Indonesia's democratic consolidation faces new challenges following the Constitutional Court's decision to eliminate the presidential threshold, fundamentally altering the political landscape and potentially affecting national defense mechanisms. In an era where political fragmentation can undermine governmental effectiveness and national security, understanding the relationship between electoral reforms and defense capabilities becomes crucial for maintaining state sovereignty. This research aims to develop a comprehensive model for strengthening national defense in response to the elimination of the presidential threshold to realize inclusive democracy. The method used is a mixed-method approach, combining qualitative analysis with NVivo 12 software and quantitative analysis using SEM PLS-4. The results of the research show that politics and democracy significantly affect National Defense, with a coefficient of 0.468 and a p-value of 0.023, which indicates a significant effect at the 5% significance level. This indicates that political stability and democracy have a greater role in forming national defense. The model of strengthening the coalition system in parliament can encourage inter-party consensus to maintain government stability, ensure that defense policies continue to operate, maintain the neutrality of the TNI, keep the National Police consistent and committed to state security, and maintain society's role in overseeing politics and democracy. This research contributes to defense policy literature by providing empirical evidence of how electoral system changes impact national security frameworks, offering practical insights for policymakers navigating democratic transitions while maintaining effective defense capabilities.